On Being the ‘Fat Person’: Possibilities and Pitfalls for Fat Activist Engagement in Academic Institutions - Evans, Calla; Friedman, May (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
This article addresses the possibilities and pitfalls for fat activist engagement in academic institutions through the framework of the ‘fat person.’ Drawing from Emily Henderson’s (2019) ‘gender person’ in academia framework, we connect our own experiences as fat studies scholars, teachers, and activists with the experiences of other scholars in our field to construct a framework of understanding the role of the fat studies expert, or the ‘fat person,’ in the academy. The raw material for this article was written over the course of two extended online chat sessions between the authors, which took place during the summer of 2020. Our conversations were seeded by our prior histories as fat people and fat academics, and by our pre-existing collaborations: as supervisor and graduate student, co-researchers, and through teaching together in a fat studies course. Throughout this article we draw on scholars in our field who have explored their experiences as fat academics, fat researchers, fat students, and fat teachers. We argue that this framework is a useful step in furthering understanding of what it means to be positioned as the ‘fat person’ within an academic institution. We are embedded in the strength of our communal and embodied experiences, and at the same time, we are also aware of the potential ethical challenges of working from a place that is firmly grounded in community knowledge. Our hope is that other scholars, particularly fat studies scholars, will build from the framework we are suggesting here to further understandings of how the ‘fat person’ is constructed—and resisted—within the academy.